Small molecular glucokinase activators: has another new anti-diabetic therapeutic lost favour? - Rees, MG; Gloyn, A (2013)
UNLABELLED: Glucokinase activators (GKAs) represent one of the leading hopes for the next generation of type 2 diabetes (T2D) therapeutics, showing efficacy in reducing blood glucose and HbA1c levels in animal models of T2D and short-term human trials. While the hypoglycaemic risks of GCK activation in pancreatic beta-cells have long been appreciated, the hepatic effects of GKAs have generally been perceived to be without significant side effect. In this issue of the British Journal of Pharmacology, De Ceuninck et al. report that acute and chronic GKA treatment of normoglycaemic and hyperglycaemic rodent models results in significant accumulation of triglycerides in the liver. This suggests GKA-mediated activation of hepatic glucose uptake and suppression of endogenous glucose production may come at a significant cost; namely, the development of hepatic steatosis. This raises important questions regarding the safety of GKAs and emphasizes that both plasma and hepatic lipid profiles should be carefully monitored in on-going and future studies of these molecules. LINKED ARTICLE: This article is a commentary on De Ceuninck et al., pp. 339-353 of this issue. To view this paper visit http://dx.doi.org/10.1111/j.1476-5381.2012.02184.x.